2016
DOI: 10.5665/sleep.5464
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime Variability and Metabolic Health in Midlife Women: The SWAN Sleep Study

Abstract: A commentary on this article appears in this issue on page 269.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 50 publications
0
47
0
Order By: Relevance
“…42,43 Moreover, irregular sleep-wake patterns including variability in nocturnal sleep duration and daytime napping have also been associated with obesity independent of mean sleep duration in both men and women. 44,45 Recently, studies have also demonstrated that overweight and obesity are more common in shi-workers than day workers possibly as an outcome of physiological maladaptation to chronically sleeping and eating at abnormal circadian times. 46,47 In the similar manner, our study also demonstrates signicant association of inadequate sleep, irregular sleep-wake timings, and shi-work with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Moreover, irregular sleep-wake patterns including variability in nocturnal sleep duration and daytime napping have also been associated with obesity independent of mean sleep duration in both men and women. 44,45 Recently, studies have also demonstrated that overweight and obesity are more common in shi-workers than day workers possibly as an outcome of physiological maladaptation to chronically sleeping and eating at abnormal circadian times. 46,47 In the similar manner, our study also demonstrates signicant association of inadequate sleep, irregular sleep-wake timings, and shi-work with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent shifts in sleep timing were associated with metabolic problems and increased prevalence of depressive symptoms [18,19]. However, the literature on effects of bedtime on sperm health is scant.…”
Section: Discussionmentioning
confidence: 99%
“…Several related, yet distinct dimensions of sleep, such as restricted sleep (Buxton et al, 2010; Spiegel et al, 1999), short sleep (Cappuccio et al, 2010; Malone et al, 2016), late chronotype (Merikanto et al, 2013) and irregular sleep times (Taylor et al, 2016; Wong et al, 2015) have been associated with cardio-metabolic diseases. Hypertension is more prevalent in persons reporting short sleep (≤6 h), independent of socioeconomic status (Stranges et al, 2010).…”
Section: Introductionmentioning
confidence: 99%